CARDIOPULMONARY AND BLOOD GAS PARAMETERS IN SHEEP UNDER INHALATIONAL ANESTHESIA DURING DECUBITUS ALTERNATIONS - Liana Villela Gouvea; João Gabriel César Palermo; José Renato Junqueira Borges; Ricardo Miyasaka Almeida; Fábio Henrique Bezerra Ximenes; Roberta Ferro de Godoy (Ciência Animal Brasileira, 2016)
Sheep herds, especially Santa Ines breed, have grown in the Brazilian Midwest in recent years. Therefore, clinical cases have also grown, and along came the need of conducting major surgeries without pain associated with the use of inhalational anesthesia. This study evaluated the cardiopulmonary and blood gas parameters in sheep under inhalational anesthesia with controlled ventilation, and assessed the effect of decubitus alternations on the parameters. The animals were anesthetized with acepromazine and propofol, intubated and placed on inhalational anesthesia with isoflurane. The respiratory rates, blood pressure and blood gas concentrations were measured every for minutes for a total of 45 minutes during which the animals were alternated right, dorsal and left decubitus. The measured parameters showed no significant differences among the times and positions, concluding that inhalational anesthesia with isoflurane is valid and safe for sheep, as it keeps the cardiopulmonary parameters and arterial blood gases at safe levels. Keywords: blood gas; decubitus; surgery.